2020
DOI: 10.1128/msphere.00180-20
|View full text |Cite
|
Sign up to set email alerts
|

Subtle Variations in Dietary-Fiber Fine Structure Differentially Influence the Composition and Metabolic Function of Gut Microbiota

Abstract: The chemical structures of soluble fiber carbohydrates vary from source to source due to numerous possible linkage configurations among monomers. However, it has not been elucidated whether subtle structural variations might impact soluble fiber fermentation by colonic microbiota. In this study, we tested the hypothesis that subtle structural variations in a soluble polysaccharide govern the community structure and metabolic output of fermenting microbiota. We performed in vitro fecal fermentation studies usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 15 publications
1
42
0
Order By: Relevance
“…Dietary fibers that reach the lower bowel undigested can become substrates for microbial hydrolytic enzymes, releasing bound compounds and nutrients that can be utilized by the body (Tannock, 2020; Tungland & Meyer, 2002). The amount, chemical nature, and physical form of dietary fibers arriving in the lower gut are the principle drivers of the composition/diversity of the gut microbiome (Ho Do et al., 2020; Tamura & Brumer, 2021; Tuncil et al., 2020) that can affect pH and composition of digesta and has been linked to health outcomes (Swanson et al., 2020; Tamura & Brumer, 2021) as discussed later in this review.…”
Section: Effects Of Whole Grains On Dietary Carbohydrate Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary fibers that reach the lower bowel undigested can become substrates for microbial hydrolytic enzymes, releasing bound compounds and nutrients that can be utilized by the body (Tannock, 2020; Tungland & Meyer, 2002). The amount, chemical nature, and physical form of dietary fibers arriving in the lower gut are the principle drivers of the composition/diversity of the gut microbiome (Ho Do et al., 2020; Tamura & Brumer, 2021; Tuncil et al., 2020) that can affect pH and composition of digesta and has been linked to health outcomes (Swanson et al., 2020; Tamura & Brumer, 2021) as discussed later in this review.…”
Section: Effects Of Whole Grains On Dietary Carbohydrate Qualitymentioning
confidence: 99%
“…Also, fine‐structural differences in XOS and arabinoxylooligosaccharides (AXOS) dictated differential growth of a number of Bacteroides species commonly found in the colon (Mendis et al., 2018). Similarly, subtle variations in the chemical fine‐structure of AXs from different classes of wheat (hard red spring, hard red winter, and spring red winter), with differences in backbone length and branching, led to the development of different community structure when incubated with fecal samples (Tuncil et al., 2020).…”
Section: Effects Of Whole Grain On Microbiota Composition and Activitymentioning
confidence: 99%
“…In nature, variation in polysaccharide structure is overwhelmingly associated with differences in the ratios of glycosyl residues that compose the polymer (starch and glycogen being notable exceptions) (22). For example, arabinoxylans extracted from bran of three classes of wheat exhibited coordinate variation in sugar composition and linkage structure (10). These variables may exert independent influences upon microbial community responses to complex substrates.…”
Section: Discussionmentioning
confidence: 99%
“…The application of heat, pressure, or mechanical forces induces oxidative and hydrolytic reactions, which both modify the native chemical structure (12)(13)(14)(15). Consequently, these structural modifications influence physicochemical properties and may further affect the prebiotic potential of AX (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…This enzymatic digestion and the resulting metabolism of released monosaccharides lead to the production of beneficial SCFA metabolites and modulates the gut environment (20)(21)(22).Various studies have shown that the in vitro fermentation of AX is strongly linked to the molecular fine structure of AX (23,24). Similarly, Tuncil et al (17) hypothesized that subtle variations in dietary fiber structures may result in altered microbiota compositions. In particular, differences in M w and the branching of soluble cereal AX affect SCFA production and bacterial growth during in vitro fermentation by human fecal microbiota (20,25).…”
Section: Introductionmentioning
confidence: 99%